ANALISIS PROFITABILITAS, UKURAN PERUSAHAAN DAN PERTUMBUHAN PENJUALAN TERHADAP NILAI PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Budiyono, Tri; Br. Purba, Neni Marlina (LPPM Universitas Putera Batam, 2021)
The purpose of this study to analyze the effect profitability, company size and sales growth on firm value in the Indonesia Stock Exchange. The population of this research is 10 pharmaceutical sector manufacturing companies listed on the Indonesia Stock Exchange in 2015-2019. This study uses a sampling technique with purposive sampling method so that there are 7 companies that meet criteria. The data in this study used secondary data obtained from the official website of the Indonesia Stock Exchange and the representative IDX office of the Riau Islands. The data collection technique used is documentation technique. The data analysis technique used the classical assumption test consisting of normality test, multicollinearity test, heteroscedasticity test and autocorrelation test. Then proceed with the use of multiple linear regression analysis and hypothesis testing consisting of partial test or T test, simultaneous test or F test and analysis of the coefficient of determination. The results showed that partially profitability and firm size had a significant effect on firm value and sales growth had no significant effect on firm value. The results of the F test show that profitability, company size and sales growth simultaneously have a significant effect on firm value.